Safety compliance for hihg rise projects in Nigerian construction Industry - Mohammed Kabir, Kaigama (2015)
Health and safety issues had always been a major challenge and concern in the construction industry. Construction is found to be one of the most dangerous on health and safety practice, predominantly in developing countries. As construction accidents continue to dominate the overall construction industry. Despite the programs implemented by government and measures introduced by companies the number of high rise construction accidents still remains alarmingly. This research aim to investigate the safety compliance for high rise construction project in Nigeria. In achieving this aim three (3) objectives has been outlined; to investigate the current level of compliance to safety practice and policies in Nigerian construction site. To investigate the factors that prevent the compliance to safety and health practices in high rise projects of Nigerian construction industry. To recommend appropriate ways to improve the compliance to safety in high rise of Nigerian construction. The interview and questionnaire method was used in this research. Structured Questionnaires was distributed to 108 potential respondents from the construction industry players 90 was returned and Qualitative interview have been conducted to meet the first objective of the project, to investigate the current level of compliance to safety practice In addition, structured interviews were carried out with selected managers from construction industry. The result shows that Bribery and corruption, Lack of training, Absence of safety representatives, Lack of corporate responsibility & Accountability, Weak legal structure were the significant factors affecting safety. Compliance. The result also indicate that Site inspection, Safety seminars (enforcement officers), Building codes of practice, Enforcement of safety act, Workers/labourers training are the effective factors that could improve compliance to safety practice in high rise project of Nigerian construction industry. It is recommended that relevant authorities should checkmate the Safety practices in the Nigerian construction industry.